Pompe Disease: Cyanosed Hypotonic Infant with Normal Respiratory Rate - Koirala, S.; Poudel, A.; Basnet, R.; Subedi, K. (Kathmandu University Medical Journal, 2017)
Infantile hypotonia or floppy infant is a diagnostic challenge when it presents with other presenting complaints such as fever, cough or diarrhea. Many times the hypotonia goes unnoticed when other symptom covers the hypotonia and child continues to receive the treatment for other symptoms. We report a rare case from Nepal of infantile Pompe disease who presented with the history of fever and cough in the recent earthquake disaster camp at remote part of Sindhupalchowk, Nepal. He was being treated as a case of pneumonia. Pompe disease can be diagnosed clinically by taking detailed history and correlating the clinical findings during the presentation with other symptoms. In our case the normal respiratory rate, reduced Spo2 and presence of crackles dominated the hypotonia and was mistreated as pneumonia. High index of suspicion is necessary in diagnosing Pompe disease.